2020
DOI: 10.3349/ymj.2020.61.12.1054
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Myomectomy versus Abdominal Myomectomy for Large Myomas Sized over 10 cm or Weighing 250 g

Abstract: ic myomas who are unresponsive to medical treatment, myomas compressing the adjacent organs, or myomas associated with subfertility are candidates for hysterectomy or myomectomy. Myomectomy is the fertility-preserving surgical option. However, the original myomectomy surgical technique, abdominal myomectomy (AM), is associated with larger abdominal incision, more postoperative pain, more analgesic use, longer hospital stay, and higher risk of postoperative pelvic adhesion compared to minimally invasive surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The initial pool of 955 studies, which resulted from the preliminary search of the medical databases, was refined via manual screening of the title and abstract, leading to 107 reports being moved to full-text assessment. Through constant evaluation and strict application of the pre-established inclusion criteria, 53 studies were ultimately included in this review [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This systematic process of selection is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The initial pool of 955 studies, which resulted from the preliminary search of the medical databases, was refined via manual screening of the title and abstract, leading to 107 reports being moved to full-text assessment. Through constant evaluation and strict application of the pre-established inclusion criteria, 53 studies were ultimately included in this review [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This systematic process of selection is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The study reported that RM was associated with less EBL and a lower risk of blood transfusion than AM; however, no significant difference was found between RM and LM [34]. A recent study comparing RM (n = 126) and AM (n = 151) for large myomas (>10 cm or 250 g) observed no difference in EBL between the two groups [35]. A recent meta-analysis including a total of 2027 patients found no significant difference between RM and LM in terms of OT, EBL, blood transfusion, length of hospital stay, complications, and postoperative fertility [21].…”
Section: Previous Reports On Ebl and Total Ot In Rmmentioning
confidence: 94%
“…The use of RALM has several advantages which allows the articulation of instruments by 540° as well as easier intracorporeal suturing. It also may considered in complex surgical cases for which traditional laparoscopy is not indicated [66]. It should be clearly stated that RALM constitutes the minimally invasive alternative to open myomectomy in those cases that cannot be adequately and consistently addressed with conventional minimally invasive surgery [52].…”
Section: Open Vs Laparoscopic Myomectomymentioning
confidence: 99%